Research on Pricing and Battery Performance Enhancement Decisions of the New Energy Vehicle Supply Chain Under Different Subsidy Strategies (Contemporary Mathematics, 2025)
Consumers' increasing concern about the battery performance of New Energy Vehicles (NEVs) necessitates effective government subsidies to enhance corresponding investments and  production. A subsidy strategy based on battery performance enhancement degree is proposed, and a comparative analysis with the retailer sales subsidy strategy is conducted. Our findings reveal that both subsidy strategies enhance battery performance and market demand, while a sales subsidy strategy potentially lowering the NEV price. The ratio of subsidy coefficients determines the effect of different subsidy strategies on the NEV supply chain's operational decisions. When each subsidy coefficient remains unchanged, an increase in performance sensitivity coefficient or a decrease in enhancement cost coefficient narrows the gap between the equilibrium solutions under the two subsidy strategies. Meantime, it can also further strengthen the advantages of the performance enhancement subsidy in improving member enterprises’ profits and consumer surplus. Finally, under identical government subsidy expenditures, the optimal subsidy strategy choice is closely related to the evaluation criteria.
Keywords: government subsidies; new energy vehicles; pricing decisions; battery performance enhancement